ВЗАИМОДЕЙСТВИЕ БЛИЗКОРОДСТВЕННЫХ ЯЗЫКОВ В СИТУАЦИИ ОБУЧЕНИЯ (Philological Studies, 2019)
The article considers the principles of teaching translation from closely related language intercultural communication. Shows what types of translation master students and how in the process of teaching foreign language translation of the text in their native language have contacts languages (native and non-native) and contacts crops (native and foreign). This kind of intercultural contacts contribute to the development in students of a number of competences that are necessary for improving the level of professionalism (linguistic, philological)and to deepen their “cultural awareness”, vocabulary, increase of level of knowledge of different discourse types of native language.
Keywords: theory of translation; the situation of teaching; Ukrainian language; language contacts; cross-cultural communication, Russian language